Effect of ER5183 filler rod on the metallurgical and mechanical properties of TIG-welded AA5083 and AA5754 joints. (2023) - Senthur Vaishnavan, S.; Jayakumar, K.; Naveen Kumar, P.; Suresh, T.
Abstract: Tungsten Inert Gas (TIG) welding is one of the most widely used welding procedures for joining aluminium alloys. However, welding efficiency is dependent on the welding circumstances and filler rods used. As a result, this study examined the effect of the ER5183 filler rod on the mechanical properties and metallurgical of the TIG welded AA5083 and AA5754. These two alloys combination joints are used in automobiles, shipbuilding, etc. A V-groove joint was attempted on 5 mm thick plates with a 2.4 mm diameter tungsten electrode. First, the microstructural characterization was carried out to observe grain structure in the weld sample. Mechanical properties were studied to determine the yield and ultimate tensile strength after TIG welding. Finally, a hardness study along a transverse direction of weldments was carried out at the different weld zones. The results showed that the maximum UTS of the weld joint was achieved as 169 MPa and hardness of 89 HV on the weld joint.